Ferrite system stainless steel sheet
Patent Information
- Application Number
- CN202180104257.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-11-17
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2041-11-17
AI Technical Summary
然而,专利文献4将成形速度限制为10mm/min以下,成形品的成形所需时间存在一定的限制
[0041]根据本发明,能够提供成形性优异的铁素体系不锈钢板。特别是根据本发明,在制造作为用于使家电产品、厨房设备轻量化的部件所需要的壁厚薄的成形品时,能够使用本发明的铁素体系不锈钢板作为坯料,能够发挥良好的成形性,因此能够得到满足尺寸精度、美观性的成形品。
Smart Images

Figure GDA0004840506750000121 
Figure GDA0004840506750000131 
Figure GDA0004840506750000141
Abstract
Description
Technical Field
[0001] This invention relates to ferritic stainless steel plates. Background Technology
[0002] Ferritic stainless steel sheets are widely used in household appliances, kitchen equipment, and electronic devices, but their applications are sometimes limited due to their poorer formability compared to austenitic stainless steels. However, in recent years, advancements in refining technology have made ultra-low carbonization and ultra-low nitriding of ferritic stainless steels possible. Furthermore, attempts have been made to improve the formability and corrosion resistance of ferritic stainless steels by adding elements such as Ti and Nb. In addition, as illustrated in Patent Documents 1-3, attempts have been made to improve the formability of ferritic stainless steels by controlling the composition and manufacturing methods.
[0003] By utilizing these existing improvement techniques to enhance formability, ferritic stainless steels have been increasingly used in a wide range of applications. In recent years, the increasing demand for lightweight end products has led to continuous efforts to further improve them. Specifically, to achieve lightweight end products, the aim is to obtain ferritic stainless steels with even thinner sheet thicknesses than before, while maintaining higher formability.
[0004] For example, bulging is a forming method that does not allow material to flow into the die and utilizes plastic deformation for shaping. This plastic deformation is mainly elongation deformation of the part in contact with the punch. The deformation area extends from the die shoulder to the punch head. In cylindrical forming using a die, generally, because the contact load between the material and the punch reaches its maximum around the punch shoulder, material movement is constrained, and deformation concentrates between the punch shoulder and the die shoulder, resulting in the greatest reduction in sheet thickness. Then, fracture occurs when necking occurs in this area.
[0005] For applications requiring components formed using this embossing technique, there are exterior decorative panels for home appliances and kitchens. Traditionally, these panels were made from ordinary steel that had been coated, but this resulted in issues such as paint lifting and rust at the ends. On the other hand, stainless steel's formability has improved, and its aesthetics have been enhanced through transparent coatings that achieve a high-end look. For these reasons, stainless steel has become the more common raw material for exterior decorative panels in recent years. In particular, since exterior decorative panels constitute the product's appearance, high dimensional accuracy is required. Therefore, processes such as embossing are often employed.
[0006] Furthermore, as mentioned above, there is a strong demand for lightweighting in products such as home appliances and kitchen equipment, as well as in exterior decorative panels. It is generally believed that this lightweighting can be achieved by using stainless steel sheets with a thickness of 0.4mm to 0.8mm, which is thinner than before. However, ferritic stainless steel sheets with such a thickness that meet the required embossing properties do not exist, including those in the aforementioned Patent Documents 1 to 3.
[0007] Patent document 4 describes a ferritic stainless steel sheet for exterior decorative panels, which has a specified chemical composition, a sheet thickness of 0.4–0.8 mm, a forming speed of 3–10 mm / min, and a bulge height exceeding 10 mm during Eriksen testing. However, Patent document 4 limits the forming speed to below 10 mm / min, thus limiting the forming time required for the molded product. Therefore, there is a need to further improve the productivity of the molded product.
[0008] Existing technical documents
[0009] Patent documents
[0010] Patent Document 1: Japanese Patent Application Publication No. 57-198248
[0011] Patent Document 2: Japanese Patent Application Publication No. 58-61258
[0012] Patent Document 3: Japanese Patent Application Publication No. 2004-217996
[0013] Patent Document 4: Japanese Patent No. 6050701 Summary of the Invention
[0014] The problem that the invention aims to solve
[0015] The present invention was made in view of the above circumstances, and the problem to be solved is to provide a ferritic stainless steel sheet with excellent formability.
[0016] Methods for solving problems
[0017] To address the aforementioned issues, the present invention provides the following solution.
[0018] [1] A ferritic stainless steel sheet, which contains, by mass percent:
[0019] C: Below 0.0200%
[0020] Si: below 0.70%
[0021] Mn: below 1.00%
[0022] P: below 0.030%
[0023] S: less than 0.005%
[0024] Cr: 11.0–19.5%
[0025] N: below 0.020%
[0026] Al: 0.005~0.100%
[0027] O: below 0.0050%
[0028] Ti: 0.03~0.20%
[0029] Nb: 0.010~0.300%
[0030] Sn: 0.001~0.300%
[0031] Zr: 0.001~0.080%,
[0032] The remainder contains iron and impurities.
[0033] The ferritic stainless steel plate has a composition that satisfies the following formulas (1) and (2), and the plate thickness is less than 1.0 mm, with a maximum drawing ratio of 2.30 or more in cylindrical deep drawing.
[0034] (0.4×Al+0.5×Zr+0.1×Ti) / O≥12.0 (1),
[0035] 0.6×Cr+15×Sn+8×Al≥10.0 (2),
[0036] In Equation (1) and Equation (2), the element symbols represent the content of each element in the aforementioned ferritic stainless steel plate by mass % respectively.
[0037] [2] The ferritic stainless steel plate according to [1] is characterized in that it contains one or more of the following by mass%: Mo: 0.05-0.50%, Ni: 0.05-0.50%, Cu: 0.01-1.00% to replace a portion of Fe.
[0038] [3] The ferritic stainless steel plate according to [1] or [2] is characterized in that it contains one or more of the following by mass%: B: 0.0003 to 0.0050%, Ga: 0.0001 to 0.2%, and W: 0.001 to 0.300% to replace a portion of Fe.
[0039] [4] The ferritic stainless steel sheet according to any one of [1] to [3] is characterized in that the average Lankford value is 1.8 or more and the in-plane anisotropy (Δr) of the Lankford value is 0.5 or more.
[0040] Invention Effects
[0041] According to the present invention, ferritic stainless steel sheets with excellent formability can be provided. In particular, according to the present invention, when manufacturing thin-walled molded articles required for components used to reduce the weight of household appliances and kitchen equipment, the ferritic stainless steel sheets of the present invention can be used as blanks, exhibiting good formability, and thus molded articles that meet dimensional accuracy and aesthetic requirements can be obtained. Detailed Implementation
[0042] In order to improve the formability of ferritic stainless steel sheets, which are generally considered to have lower formability compared to austenitic stainless steel sheets, and to obtain aesthetically pleasing molded products without cracking or poor forming, the inventors have conducted in-depth research.
[0043] Generally, the lower the yield strength ratio of the steel sheet being formed, the higher its machinability. The yield strength ratio is the ratio of yield stress to tensile strength. A lower yield strength ratio allows for a larger load range in the uniform elongation region, making it easier to perform plastic processing. On the other hand, for example, in deep drawing of cylinders, the thickness distribution of the steel sheet increases during forming, promoting thickness reduction and making it easier for cracks to originate from internal inclusions. Therefore, in order to impart formability suitable for deep drawing of cylinders, the inventors investigated the relationship between the types and contents of various elements in ferritic stainless steel and formability. Deep drawing of cylinders is a challenging forming process, and suppressing thickness reduction at stress concentration points is effective in improving formability. Once thickness reduction occurs, machinability decreases with work hardening. Detailed observation of the cross-section of formed articles that developed cracks during forming revealed multiple Al oxides and TiN. Considering that these Al oxides and TiN promote cracking, a steel composition that can suppress the uneven distribution of Al oxides and the growth of TiN was investigated. Furthermore, it was discovered that by using steel plates with specific steel compositions as blanks for deep drawing, forming that meets dimensional accuracy requirements can be achieved.
[0044] The following describes the ferritic stainless steel sheet according to an embodiment of the present invention.
[0045] The ferritic stainless steel plate of this embodiment is a steel plate containing, by mass %: C: 0.0200% or less, Si: 0.70% or less, Mn: 1.00% or less, P: 0.030% or less, S: 0.005% or less, Cr: 11.0 to 19.5%, N: 0.020% or less, Al: 0.005 to 0.100%, O: 0.0050% or less, Ti: 0.03 to 0.20%, Nb: 0.010 to 0.300%, Sn: 0.001 to 0.300%, Zr: 0.001 to 0.080%, with the balance being iron and impurities. The steel plate has a composition that satisfies the following formulas (1) and (2), and the plate thickness is 1.0 mm or less, and the limiting drawing ratio in cylindrical deep drawing is 2.30 or more.
[0046] (0.4×Al+0.5×Zr+0.1×Ti) / O≥12.0 (1)
[0047] 0.6×Cr+15×Sn+8×Al≥10.0 (2)
[0048] Wherein, the element symbols in formulas (1) and (2) represent the content of each element in the aforementioned ferritic stainless steel plate by mass%.
[0049] In addition, ferritic stainless steel plates may contain one or more of the following by mass percent: Mo: 0.05-0.50%, Ni: 0.05-0.50%, Cu: 0.01-1.00% to replace a portion of Fe.
[0050] Furthermore, ferritic stainless steel plates may contain one or more of the following by mass percentage: B: 0.0003–0.0050%, Ga: 0.0001–0.2%, and W: 0.001–0.300% to replace a portion of Fe.
[0051] This section explains the rationale behind specifying the chemical composition of ferritic stainless steel sheets. It should be noted that, unless otherwise specified, the percentage (%) for component content indicates mass.
[0052] C: Below 0.0200%
[0053] For reasons of deteriorating formability and corrosion resistance, the content of carbon (C) should be as low as possible, with an upper limit set below 0.0200%. However, since excessive reduction in C content leads to increased refining costs, it is ideal to set a lower limit of C content above 0.0010%. A preferred C content is 0.0030% to 0.0070%.
[0054] Si: below 0.70%
[0055] Si is sometimes present as a deoxidizing element, and since it is a solid solution strengthening element, its content should be as low as possible from the perspective of reducing yield stress, with an upper limit set below 0.70%. However, excessive reduction in Si content will lead to increased refining costs, so ideally, the lower limit should be set above 0.01%. The preferred Si content is 0.05% to 0.50%.
[0056] Mn: below 1.00%
[0057] Like Si, Mn is a solid solution strengthening element; therefore, from the perspective of reducing yield stress, its content should be as low as possible, with an upper limit set below 1.00%. However, excessive reduction in Mn content will lead to increased refining costs, so ideally, the lower limit should be set above 0.01%. The preferred Mn content is 0.05% to 0.50%.
[0058] P: below 0.030%
[0059] Phosphorus (P) is an element that inevitably mixes in from the raw materials. Furthermore, like Si and Mn, it is a solid solution strengthening element; therefore, its content should be as low as possible. From the perspective of elongation, the upper limit is set to 0.030% or less. Preferably less than 0.030%, more preferably 0.025% or less. However, excessive reduction in P content will lead to increased refining costs; therefore, the lower limit can be set to 0.010% or more.
[0060] S: less than 0.005%
[0061] In titanium-containing steels, sulfur (S) forms Ti₄C₂S₂ with Ti and C, which helps to immobilize C. Ti₄C₂S₂ is a coarse precipitate formed at high temperatures, thus having little impact on recrystallization and grain growth. However, if a large amount of this precipitate forms, it can become the starting point for rusting, deteriorating corrosion resistance. Therefore, the upper limit for S is set below 0.005%. However, excessive reduction in S content leads to increased refining costs, so the lower limit for S content can be set above 0.0001%.
[0062] Cr: 11.0–19.5%
[0063] To improve corrosion resistance, Cr needs to contain at least 11.0%, but excessive Cr will not only degrade toughness and manufacturability, but also increase yield stress. Therefore, the upper limit of Cr is set at 19.5% or less. The preferred Cr content is 13.0% to 17.5%.
[0064] N: below 0.020%
[0065] Since nitrogen (N), like carbon (C), degrades formability and corrosion resistance, its content should be as low as possible; therefore, the upper limit is set to below 0.020%. However, from the perspective of reducing manufacturing costs, the lower limit can be set to above 0.003%. The preferred N content is 0.005% to 0.015%.
[0066] Al: 0.005~0.100%
[0067] Al, as a deoxidizing element, can be present at a concentration of 0.005% or more. On the other hand, excessive Al content can reduce formability and weldability, and may also lead to surface quality deterioration; therefore, the upper limit is set to 0.100% or less. The preferred Al content is 0.010% to 0.080%.
[0068] O: below 0.0050%
[0069] O (O) reduces corrosion resistance and processability. Therefore, the amount of O needs to be kept low, with the upper limit set below 0.0050%. However, excessively reducing the amount of O will increase refining costs, so the lower limit of the O amount can be set above 0.0001%. The preferred range for the O amount is 0.0005% to 0.0030%.
[0070] Ti: 0.03~0.20%
[0071] Ti combines with C, N, and S to form inclusions, which improve corrosion resistance, resistance to intergranular corrosion, and deep drawing ability; therefore, it is contained at 0.03% or more. On the other hand, Ti is a solid solution strengthening element, so excessive Ti content leads to an increase in dissolved Ti, resulting in a decrease in elongation, an indicator of bulging properties. Therefore, the upper limit of Ti is set to 0.20% or less. The preferred Ti content is 0.08% to 0.12%.
[0072] Nb: 0.010~0.300%
[0073] Nitrogen (Nb) is an element that improves formability and corrosion resistance, and its effect is achieved by containing more than 0.010%. However, excessive content can lead to a decrease in ductility caused by solid solution strengthening, so it is set to 0.300% or less. The preferred Nb content is 0.100% to 0.200%.
[0074] Sn: 0.001~0.300%
[0075] Sn has the effect of reducing the yield strength ratio and improving the processability of embossed parts by including it. To achieve this effect, the Sn content should be 0.001% or more. On the other hand, excessive Sn will degrade manufacturability, so the upper limit is set to 0.300% or less. The preferred Sn content is 0.020% to 0.200%.
[0076] Zr: 0.001~0.080%
[0077] Zr is present at a content of 0.001% or more as a deoxidizing element. On the other hand, excessive Zr content can lead to deterioration of formability, weldability, and surface quality; therefore, the upper limit is set to 0.080% or less. The preferred Zr content is 0.002% to 0.020%.
[0078] (0.4×Al+0.5×Zr+0.1×Ti) / O≥12.0
[0079] Upon close examination of the cross-section of the formed article with cracks, Al oxides present at the bottom of most of the dimples and blocky TiN unrelated to the dimples can be observed. These serve as crack initiation points or promote crack propagation. To suppress the uneven distribution of Al oxides and the growth of TiN, improving the inclusion composition is effective, and utilizing Zr as a strong deoxidizer is effective. A detailed investigation was conducted on the relationship between the contents of Al, Ti, O, and Zr and crack formation. The results showed that when (0.4×Al+0.5×Zr+0.1×Ti) / O is 12.0 or higher, excellent formability is exhibited. Therefore, the ferritic stainless steel sheet of this embodiment preferably satisfies (0.4×Al+0.5×Zr+0.1×Ti) / O≥12.0.
[0080] 0.6×Cr+15×Sn+8×Al≥10.0
[0081] To improve the formability of deep-drawn cylinders, it is necessary to suppress wrinkling of the flanges, wrinkling of the incoming material, and thickness increase at the end of processing. Ferritic stainless steel, due to its low fracture strength, cannot improve wrinkle resistance; therefore, high lubrication is an effective strategy. High lubrication typically involves using lubricants, but at the end of forming, the surface pressure between the material and the die is very high, causing the lubricant to be expelled. Under processing conditions where the lubricant's effect is minimal, the influence of the material's surface film and concentration distribution becomes significant. A passivation film exists on stainless steel, and phenomena such as the enrichment of oxides generated during the manufacturing process on the surface layer occur, resulting in diverse elemental concentration distributions. Cr is an indispensable element in the formation of the passivation film, and since the die and die coating often contain Cr, their combination can lead to die sticking due to affinity. Therefore, by including Al, which forms strong oxides, in the passivation film, die sticking can be suppressed, ensuring stable formability. Furthermore, Sn readily exists on the surface and is softer than other elements, thus playing a role in mitigating stress concentration. A detailed investigation was conducted on the relationship between the contents of Cr, Al, and Sn and the ultimate drawing ratio. The results showed that when the content of 0.6×Cr+15×Sn+8×Al is 10.0 or higher, the ultimate drawing ratio stably exceeds 2.30. Therefore, the ferritic stainless steel sheet of this embodiment preferably satisfies 0.6×Cr+15×Sn+8×Al≥10.0.
[0082] Furthermore, the ferritic stainless steel plate of this embodiment may contain one or more of the following by mass percentage: Mo: 0.05-0.50%, Ni: 0.05-0.50%, Cu: 0.01-1.00% to replace a portion of Fe.
[0083] Mo, Ni, and Cu are elements that improve corrosion resistance. In applications requiring corrosion resistance, one or more of these elements may be included as needed. Corrosion resistance is improved by including 0.05% or more of Mo and Ni. Excessive content of Mo and Ni can lead to hardening and deterioration of formability; therefore, their content is set to a maximum of 0.50% or less. Preferred Mo and Ni contents are 0.10% to 0.30%. Furthermore, Cu exhibits its effect by including 0.01% or more, but excessive Cu content can lead to deterioration of formability, especially ductility; therefore, the maximum Cu content is set to 1.00% or less. Preferred Cu contents are 0.30% to 0.80%.
[0084] Furthermore, the ferritic stainless steel plate of this embodiment may contain one or more of the following by mass percentage: B: 0.0003 to 0.0050%, Ga: 0.0001 to 0.2%, and W: 0.001 to 0.300% to replace a portion of the Fe.
[0085] Boron (B) is an element that improves secondary processing properties, and can be present at levels of 0.0003% or higher as needed. However, excessive B content leads to a decrease in elongation, therefore the upper limit is set to below 0.0050% when B is present. The preferred B content is 0.0010–0.0020%.
[0086] Ga is an element that forms GaS to improve corrosion resistance. It is also highly effective in eliminating rust initiation points by suppressing MnS precipitation. The effect cannot be confirmed at concentrations below 0.0001%, therefore, Ga can be present at concentrations above 0.0001%. However, excessive Ga content can lead to solid solution strengthening. Therefore, the upper limit for Ga content is set at 0.2% or less.
[0087] Like Nb and Ti, W is an element that fixes C and N to prevent sensitization caused by Cr carbonitrides and improve corrosion resistance. To achieve this effect, the W content can be set to 0.001% or more. On the other hand, if the W content exceeds 0.300%, it will cause the stainless steel sheet to harden and reduce its workability. Therefore, it is preferable to set the W content to 0.300% or less.
[0088] The ferritic stainless steel sheet of this embodiment contains Fe and impurities (including unavoidable impurities) in addition to the elements described above. Furthermore, other elements may be included beyond those described above, provided they do not impair the effects of the present invention. In this embodiment, for example, Bi, Pb, Se, and H may be included, but in this case, it is preferable to minimize their content. On the other hand, the proportions of these elements are controlled to the extent necessary to solve the problems of the present invention; as needed, Bi may be contained at 0.01% or less, Pb at 0.01% or less, Se at 0.01% or less, and H at 0.01% or less.
[0089] The forming method of this embodiment uses ferritic stainless steel sheets with a thickness of 1.0 mm or less as the forming object. A preferred sheet thickness is 0.4 to 0.8 mm. The ferritic stainless steel sheet of this embodiment, through adjustment of its chemical composition, becomes a steel sheet with excellent bulging properties, and is therefore particularly suitable for applications such as home appliances and kitchen equipment that require forming processes with thin sheet thicknesses.
[0090] The maximum drawing ratio in deep drawing of cylinders is 2.30 or higher.
[0091] To increase the ultimate drawing ratio in cylindrical deep drawing, a larger billet diameter relative to the diameter of the formed part is required. Ferritic stainless steel has a high r-value suitable for deep drawing, but on the other hand, it has low fracture strength, and if the material flow from the flange is slow, cracks will occur on the sidewalls. High lubrication conditions are applied to promote material flow from the flange, but with a large billet diameter, the contact length with the flange becomes longer, making lubrication failure more likely to occur towards the end of processing. In this application, a range of compositions is defined that can achieve the desired effect even under lubrication failure at the end of processing, with an ultimate drawing ratio of 2.30 or higher for which this effect is clearly achieved.
[0092] The limiting drawing ratio in cylindrical deep drawing is determined through the following steps. Prepare circular blanks of various diameters with a thickness of 0.8 mm. Perform cylindrical deep drawing on each blank using a die with the following shape: Die: inner diameter 43 mm, die radius 4 mm, punch: diameter 40 mm. Set the anti-wrinkle clamping force to 10 kN. Then, determine the maximum diameter Dmax of the blank that can be formed without breakage. The ratio of Dmax to the punch diameter d (Dmax / d) is taken as the limiting drawing ratio.
[0093] Furthermore, in this embodiment, the ferritic stainless steel sheet preferably has an average Lankford value (hereinafter referred to as the average r value, also known as the average plastic strain ratio) of 1.8 or more, and an in-plane anisotropy (Δr) of the Lankford value of 0.5 or more or greater than 0.7. By making the average r value 1.8 or more, during forming using a punch and die, the reduction in sheet thickness at the punch shoulder is less likely to occur, and the resistance to width shrinkage deformation at the flange portion is reduced, thus suppressing the generation of cracks during forming. In addition, by making the in-plane anisotropy (Δr) 0.5 or more, the in-plane anisotropy of flange deformation during forming is increased, and the sheet thickness at the flange portion varies, thereby creating an area that ensures lubrication, thus further improving formability.
[0094] The mean r value and Δr can be determined according to the plastic strain ratio test method in JIS Z2254:2008. The mean r value can be determined according to JIS Z2254:2008 using the following formula (A). In addition, the in-plane anisotropy (Δr) can be determined according to JIS Z2254:2008 using the following formula (B).
[0095] Average r value = (r0 + 2r) 45 +r 90 ) / 4(A)
[0096] Δr=(r0-2r 45 +r 90 ) / 2(B)
[0097] In equations (A) and (B), r0 represents the value of r in the rolling direction, r 90 The value of r represents the rolling direction at the right angle. 45 This indicates the r value in the 45-degree rolling direction.
[0098] The ferritic stainless steel sheet of this embodiment can be manufactured using conventional methods without particular limitations. That is, it can be manufactured by casting a billet with the desired chemical composition using steelmaking and continuous casting, followed by hot rolling, hot-rolled annealing and pickling, cold rolling, and final cold-rolled annealing. However, to improve the ultimate drawing ratio and to achieve an optimal range for the average r-value and in-plane anisotropy (Δr), it is preferable to set the cold rolling rate to a range of 78-94%, the heating rate for the final annealing after cold rolling to be greater than 20°C / second, preferably less than 200°C / second, the soaking rate and soaking time for the final annealing to be in the range of 830-950°C and 30 seconds or more but less than 2 minutes, respectively, and the cooling rate from the end of soaking to 500°C to be in the range of 15-30°C / second.
[0099] When performing final annealing on stainless steel with the chemical composition of this embodiment, there is a risk that phosphorus (P) in the steel may form P precipitates during final annealing, resulting in fine precipitation. These precipitates may form a mixed-grain structure during recrystallization, adversely affecting formability. However, by performing the aforementioned cold rolling and final annealing, the limiting drawing ratio for deep drawing of cylinders is 2.30 or higher, resulting in an average Lankford value of 1.8 or higher, and an in-plane anisotropy (Δr) of the Lankford value of 0.5 or higher. Therefore, ferritic stainless steel sheets with excellent formability can be obtained.
[0100] Example
[0101] The present invention will be described in more detail below through embodiments.
[0102] Ferritic stainless steels with the compositions shown in Tables 1A and 1B were smelted, cast, and hot-rolled into 5.0 mm thick hot-rolled plates. It should be noted that the balance in the compositions shown in Tables 1A and 1B is Fe and impurities. The hot-rolled plates were then annealed, pickled, cold-rolled to a thickness of 0.3–1.2 mm, annealed, pickled again, and then temper-rolled to produce the steel plates shown in Table 2.
[0103] It should be noted that for steel sheets No. 1 to 33, the cold rolling rate was as described in Table 2. The final annealing heating rate after cold rolling was set to a range greater than 20°C / second, the final annealing soaking rate and soaking time were set to a range of 830–950°C and 30 seconds–2 minutes, respectively, and the cooling rate from the end of soaking to 500°C was set to a range of 15–30°C / second. Deep drawing tests of cylinders were conducted using the steel sheets obtained in this manner.
[0104] Forming tests were conducted using an ERICHSEN 145-60 forming testing machine. Steel sheets were cut into circular shapes as blanks. The blank dimensions ranged from φ84 to 94 mm, and the following die shapes were used: die: inner diameter 43 mm, die opening radius 4 mm; punch: diameter 40 mm. The anti-wrinkle clamping force was set to 10 kN. Johnson Wax #122 was lightly applied as a lubricant to the formed surfaces. With these forming conditions fixed, the forming speed of the punch against the die was set to 20 mm / min for the forming test. It should be noted that the success of forming was determined by whether cracks occurred during deep drawing forming without residual flanges.
[0105] For the molded product, if cracks or shape defects occur, it is evaluated as NG (Not Good); if no cracks or shape defects occur, it is evaluated as OK. The results are shown in Table 2.
[0106] The 0.2% yield strength and elongation of the steel plate were determined using JIS 13B test specimens, and samples were collected from a 0° direction parallel to the rolling direction according to the conditions described in JIS Z2241. Furthermore, the average r value and Δr were measured using samples collected from the test specimens at 0°, 45°, and 90° relative to the rolling direction, under a strain of 16%.
[0107] The limiting drawing ratio in cylindrical deep drawing is determined through the following steps: Prepare circular blanks with various diameters and a thickness of 0.8 mm. Perform cylindrical deep drawing on each blank using a die with the following shape: die: inner diameter 43 mm, die opening radius 4 mm; punch: diameter 40 mm. Set the anti-wrinkle clamping force to 10 kN. Then, calculate the maximum diameter Dmax of the blank that can be formed without breakage. The ratio of Dmax to the punch diameter d (Dmax / d) is taken as the limiting drawing ratio.
[0108] As shown in Tables 1A, 1B and 2, when the molding is carried out under the conditions within the scope of the present invention, the molded article does not produce cracks or poor shape, and the aesthetics of the molded article are also good.
[0109] On the other hand, when molding is performed under conditions outside the scope of this invention, the molded article develops cracks and poor shape.
[0110]
[0111] Table 1B
[0112]
[0113] The underlined portion indicates that it is outside the scope of this invention.
[0114] Table 2
[0115]
[0116] The underlined portion indicates that it is outside the scope of the present invention or outside the scope of the preferred manufacturing conditions.
[0117] Industrial availability
[0118] This invention is industrially applicable in that it can provide ferritic stainless steel sheets with excellent formability. In particular, according to this invention, when manufacturing thin-walled molded articles required for components used to lighten household appliances and kitchen equipment, the ferritic stainless steel sheet of this invention can be used as a blank, exhibiting good formability, and thus molded articles that meet dimensional accuracy and aesthetic requirements can be obtained, making it industrially applicable.
Claims
1. A ferritic stainless steel plate, comprising, by mass percent: C: Below 0.0200% Si: below 0.70% Mn: below 1.00% P: below 0.030% S: less than 0.005% Cr:11.0~19.5%、 N: below 0.020% Al:0.005~0.100%、 O: below 0.0050% Ti: 0.03~0.20% Nb: 0.010~0.300% Sn: 0.001~0.300% Zr:0.001~0.080%, The remainder contains iron and impurities. The ferritic stainless steel plate has a composition that satisfies the following formulas (1) and (2), and the plate thickness is less than 1.0 mm, with a maximum drawing ratio of 2.30 or more in cylindrical deep drawing. (0.4×Al+0.5×Zr+0.1×Ti) / O≥12.0 (1), 0.6×Cr+15×Sn+8×Al≥10.0 (2), in, The element symbols in formulas (1) and (2) represent the content of each element in the ferritic stainless steel plate by mass % respectively.
2. The ferritic stainless steel plate according to claim 1, characterized in that, It contains one or more of the following by mass percent: Mo: 0.05-0.50%, Ni: 0.05-0.50%, Cu: 0.01-1.00% to replace a portion of Fe.
3. The ferritic stainless steel plate according to claim 1 or claim 2, characterized in that, It contains one or more of the following by mass percent: B: 0.0003-0.0050%, Ga: 0.0001-0.2%, and W: 0.001-0.300% to replace a portion of Fe.
4. The ferritic stainless steel plate according to claim 1 or claim 2, characterized in that, The average Lankford value is above 1.8, and the in-plane anisotropy (Δr) of the Lankford value is above 0.
5.
5. The ferritic stainless steel plate according to claim 3, characterized in that, The average Lankford value is above 1.8, and the in-plane anisotropy (Δr) of the Lankford value is above 0.5.
Citation Information
Patent Citations
Ferrite stainless steel with superior press formability
JP1982198248A
Ferrite stainless steel with superior bulgeability and secondary workability
JP1983061258A
A plurality of bobbins wound with yarn in a yarn removing device
JP1985050701B2
Ferritic stainless steel sheet superior in formability, and manufacturing method therefor
JP2004217996A
Ferritic stainless steel sheet
CN109072373A